Respostas

2014-04-30T14:20:39-03:00
A)    3 / 2 + V3=  

          3                     3         (
√3 - 2)          3(√3 - 2)                 3√3 - 6
----------------- =   ---------- x   --------- =   -------------------- =  ---------------------------- 
 2     +  
√3            √3 + 2      (√3 - 2)       (√3 + 2)(√3 - 2)      (√3.√3 -2√3 + 2√3 - 4)



           3√3 - 6                            3√3 - 6                 3√3 - 6
------------------------------    =     -------------   =         ---------- =    - 3√3 + 6  =  6 - 3√3
         √3²  - 0 - 4                          3 - 4                       - 1


B)   3  /  V5 +V3=           


            3                         3            (√5 - √3)              3(√5 - √3)
------------------ =    -------------  x  -------------- =    -----------------------= 
       √5 + √3              √5 + √3        (√5 - √3)         (√5 + √3)(√5 - √3)


                 3√5 - 3√3                                  3√5 - 3√3              3√5 - 3√3
--------------------------------------- =     ------------------------- =  ----------------- =
(√5.√5 - √5.√3 + √3.√5 - √3.√3)           √5²   -   0    - √3²           5 - 3



   3√5 - 3√3
---------------
       2
2014-04-30T16:26:57-03:00
A)      3     = 3 . ( 2 - √3) =      3 . ( 2 - √3)        3 . ( 2 - √3)     =     3( 2 - √3)    
    (2 + 
√3)     (2 - √3)          4 - 2√3 + 2√3 -3             4 - 3


b)       3    3 . ( √5 - √3) =     3 . ( √5 - √3)         =  3 . ( √5 - √3)  =     3( √5 - √3)    
    (√5 + √3)     (√5 - √3)       5 - √15 + √15 - 3                 5 - 3                     2